2021
DOI: 10.1021/acs.nanolett.1c00231
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Targeting Cerebral Ischemic Lesions with Cancer Cell-Inspired Nanovehicle for Ischemic Stroke Treatment

Abstract: The poor drug delivery to cerebral ischemic regions is a key challenge of ischemic stroke treatment. Inspired by the intriguing blood−brain barrier (BBB)-penetrating ability of 4T1 cancer cells upon their brain metastasis, we herein designed a promising biomimetic nanoplatform by camouflaging a succinobucol-loaded pH-sensitive polymeric nanovehicle with a 4T1 cell membrane (MPP/SCB), aiming to promote the preferential targeting of cerebral ischemic lesions to attenuate the ischemia/ reperfusion injury. In tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…Studies demonstrated that changes in tissue water content altered the histomorphology and the ratio of free water to bound water, and different transverse relaxation times T2 could be measured, while signal intensity and T2 values reflect the degree of brain edema. Our results showed an increase in T2 values after cerebral ischemia; RAPA@NPs treatment markedly reduced the T2 values in the ischemic hemisphere compared to the PBS and RAPA treatments (Figure A,B). T2 mapping is sensitive to water content and is commonly used for the noninvasive assessment of the edematous response after cerebral and myocardial ischemia-reperfusion. However, T2 values may also be affected by other factors, such as oxygenation and deoxygenation status, tissue microperfusion, and hemorrhage, which need to be studied in detail. To obtain more accurate results, the wet and dry weight of post-mortem brain tissue after 24 h of reperfusion in each group was determined to further assess the brain tissue water content, which is the gold standard technique for measuring cerebral edema.…”
Section: Resultsmentioning
confidence: 99%
“…Studies demonstrated that changes in tissue water content altered the histomorphology and the ratio of free water to bound water, and different transverse relaxation times T2 could be measured, while signal intensity and T2 values reflect the degree of brain edema. Our results showed an increase in T2 values after cerebral ischemia; RAPA@NPs treatment markedly reduced the T2 values in the ischemic hemisphere compared to the PBS and RAPA treatments (Figure A,B). T2 mapping is sensitive to water content and is commonly used for the noninvasive assessment of the edematous response after cerebral and myocardial ischemia-reperfusion. However, T2 values may also be affected by other factors, such as oxygenation and deoxygenation status, tissue microperfusion, and hemorrhage, which need to be studied in detail. To obtain more accurate results, the wet and dry weight of post-mortem brain tissue after 24 h of reperfusion in each group was determined to further assess the brain tissue water content, which is the gold standard technique for measuring cerebral edema.…”
Section: Resultsmentioning
confidence: 99%
“…EMBNs is synthesized by encapsulating pH‐sensitive succinic anhydride polymer nanoparticles (MPP/SCB) in a CCMs, so as to improve targeting and therapeutic effect of cerebral ischemia injury (Figure 5A). [ 91 ] In addition, in the drug delivery of antibiotics, the targeted drug delivery ability of antibiotics can also significantly reduce the drug dose, so as to achieve the purpose of improving the bioavailability of antibiotics. [ 72 ] The results showed that CCMs‐coated NPs significantly improved targeted cell uptake due to homologous targeting compared with simple NPs and other membrane‐encase NPs.…”
Section: Advantages and Applications Of Embns In Nanomedicinementioning
confidence: 99%
“…(A) The preparation of MPP/SCB and the mechanism of its therapeutic effect. [ 91 ] Reproduced with permission from Ref. [91].…”
Section: Advantages and Applications Of Embns In Nanomedicinementioning
confidence: 99%
“…Common antioxidant drugs contain Tempol ( Hosoo et al, 2017 ), edaravone (EDV) ( Jin et al, 2017 ), succinobucol ( He et al, 2021b ), and curcumin ( Wang et al, 2019 ), which were extracted naturally from plants or artificially synthesized. NPs as a feasible strategy extend the half-life of these drugs and improve their ability to cross the BBB, so improve the therapeutic effect of these drugs of ischemic stroke.…”
Section: The Nanoparticles As Drug Carriers In Ischemic Strokementioning
confidence: 99%
“…SCB has the capacity of preventing the mitochondrial dysfunction induced by tert-butyl hydroperoxide, which provides lines of evidence to clarify SCB as a potential neuroprotective agent ( Colle et al, 2013 ). A SCB-loaded pH-sensitive polymeric nanovehicle with a 4T1 cell membrane (MPP/SCB) ( He et al, 2021b ), improves the ability to penetrate the BBB and increases the targeting effect of cerebral ischemic lesions. The fluorescence signals of ROS in PC12 cells treated with MPP/SCB was significantly weaker.…”
Section: The Nanoparticles As Drug Carriers In Ischemic Strokementioning
confidence: 99%